Analisis pertimbangan Hakim dalam Memutus Tindak Pidana Pencemaran Nama Baik Melalui Sarana Elektronik - maulida Alawiyah, Mila (Parhesia, 2024)
The profession of a judge is a noble profession. Its decisions are expected to provide a sense of justice for all parties. Not only limited to realizing legal certainty. The researcher conducted a study on Decision Number 691/Pid.Sus/2020/PN Mtr concerning defamation. The purpose of this study is to contribute ideas to the development of criminal law in general and the crime of defamation, in particular. This research is a normative study using a statutory, conceptual, and case approach. The results of the study show that judges in making decisions are required to explore, follow, and understand the legal values ​​and sense of justice that live in society. This article directs judges that judges must be able to understand the background, sociology of law and cultural anthropology that exist in an area. This is because various beliefs and values ​​are still alive, believed, practiced and considered as law in a number of areas. Thus, the decision will not only provide legal protection for victims, but also for society